The UIM domain of Hrs couples receptor sorting to vesicle formation - Paula Row (Journal of Cell Science, 2003)
Hepatocyte growth factor regulated tyrosine kinase substrate (Hrs), a main component of the 'bilayered' clathrin coat on sorting endosomes, was originally identified as a substrate of activated tyrosine kinase receptors. We have analysed Hrs phosphorylation in response to epidermal growth factor (EGF) stimulation and show that the evolutionary conserved tyrosines Y329 and Y334 provide the principal phosphorylation sites. Hrs is proposed to concentrate ubiquitinated receptors within clathrin-coated regions via direct interaction with its UIM (ubiquitin interaction motif) domain. We show that the same UIM domain is necessary for EGF-stimulated tyrosine phosphorylation of Hrs. Over-expression of wild-type Hrs or a double mutant, Y329/334F, defective in EGF-dependent phosphorylation, both substantially retard EGF receptor (EGFR) degradation by inhibiting internal vesicle formation and thereby preventing EGFR incorporation into lumenal vesicles of the multivesicular bodies. In contrast, mutation or deletion of the Hrs-UIM domain strongly suppresses this effect. In addition the UIM-deletion and point mutants are also observed on internal membranes, indicating a failure to dissociate from the endosomal membrane prior to incorporation of the receptor complex into lumenal vesicles. Our data suggest a role for the UIM-domain of Hrs in actively retaining EGFR at the limiting membrane of endosomes as a prelude to lumenal vesicle formation.